Does global warming really exist? (Research, Society and Development, 2022)
The influence of temperature on organisms is one of the essential aspects for the regulation and maintenance of life. Over geological time, the temperature on Earth has fluctuated between extremes, because of natural geological phenomena. However, especially since the 20th century, some anthropic activities are altering the climate, causing temperature fluctuations on the planet. As a result of these fluctuations, a series of changes in ecological systems have been perceived and recorded, putting life on the planet at risk. In the hope of proposing alternatives to solve this problem, the Intergovernmental Panel on Climate Change (IPCC) was created, an international body that publishes assessment reports about climate change. The sixth report is currently being prepared, with some results published in the years 2021 and 2022. The present work aimed to investigate the existence of global warming from the analysis of the IPCC reports, in addition to its consequences for Latin America. The results of the reports point to the need for an urgent change in the current energy matrix based on the burning of fossil fuels, for the use of renewable energies, with increased investments for adaptation and mitigation. In addition, documents prepared by the United Nations Environment Program (UNEP) corroborate the IPCC indications the 2030 Agenda with the goals of sustainable development (SDG).